DESIGN OF CLEAN WATER AND WASTEWATER INSTALLATION SYSTEM IN CWI-1 TOWER 3, ITS SURABAYA - Angga Yostian; Ratih Indri Hapsari (Jurusan Teknik Sipil Politeknik Negeri Malang, 2026)
Water equity is critical to sustainable development and requires, among other things, sound resource use, environmental stewardship, and resilience to scarcity. This research focuses on the CWI-1 Building, Tower 3, on the ITS Surabaya campus; the goals are to estimate clean water demand and wastewater discharge, design the system layouts, interpret pipe sizes and tanks capacities, and develop a cost budgeting plan. Clean water demands are estimated from the total floor area to estimate occupancy, and then pipe sizes, ground, and roof tank capacities are calculated. Wastewater discharge is estimated using the Plumbing Fixture Unit (PFU) method, and pipe sizes are derived from the PFU calculations. The results show a total clean water demand of 170 m³/day, with a peak hourly flow of 34.03 m³/hour and peak minutes flow of 1.7 m³/min. The clean water system uses pipe sizes of ¾ in, 2 in, and 5 in. The groundwater tank capacity is calculated to be 36 m³ (6 × 3 × 2 m), and the roof water tank at 39.7 m³, though optimized to 20 m³ for cost efficiency. Wastewater discharge amounted to 9.97 m³/day, consisting of 1.77 m³/day blackwater and 8.2 m³/day greywater. The wastewater system uses 2-inch and 4-inch pipes. Blackwater is managed with a single septic tank of 5 m³/day capacity, while greywater is treated using two tanks of 8 m³/day each. The total estimated cost for the clean water and wastewater systems is Rp. 2,002,400,000